Sex differences in the development of mild cognitive impairment and probable Alzheimer's disease as predicted by hippocampal volume or white matter hyperintensities. (4th March 2019) - Burke, Shanna L.; Hu, Tianyan; Fava, Nicole M.; Li, Tan; Rodriguez, Miriam J.; Schuldiner, Katie L.; Burgess, Aaron; Laird, Angela
ABSTRACT: This study examined biological sex differences in the development of mild cognitive impairment (MCI) and probable Alzheimer's disease (AD) development as predicted by changes in the hippocampus or white matter hyperintensities. A secondary data analysis of the National Alzheimer's Coordinating Center Uniform Data Set was conducted. We selected samples of participants with normal cognition at baseline who progressed to MCI ( n = 483) and those who progressed to probable AD ( n = 211) to determine if hippocampal volume or white matter hyperintensities (WMH) at baseline predicted progression to probable AD or MCI and whether the rate of progression differed between men and women. The survival analyses indicated that changes in hippocampal volumes affected the progression to probable AD (HR = 0.535, 95% CI [0.300–0.953]) only among women. White men had an increased rate of progression to AD (HR = 4.396, CI [1.012–19.08]; HR = 4.665, 95% CI [1.072–20.29]) compared to men in other race and ethnic groups. Among women, increases in hippocampal volume ratio led to decreased rates of progressing to MCI (HR = 0.386, 95% CI [0.166–0.901]). Increased WMH among men led to faster progression to MCI (HR = 1.048. 95% CI [1.011–1.086]). Women and men who were older at baseline were more likely to progress to MCI. In addition, results from longitudinal analyses showed that women with a higher CDR global score, older age at baseline, or more disinhibition symptoms experienced higher odds of MCI development. Changes in hippocampal volumes affect the progression to or odds of probable AD (and MCI) more so among women than men, while changes in WMH affected the progression to MCI only among men.